TINDAK TUTUR DIREKTIF DALAM FILM ANIMASI JUMBO - Amalia Zahra, Razita; Ulfah, Anisa; Marzuqi, Iib (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Directive speech acts are a form of illocutionary speech act used by speakers to influence their interlocutors to take an action. This research is motivated by the diverse forms of directive speech acts in the dialogue between characters in the animated film Jumbo and the lack of research specifically examining this aspect. This study aims to describe the forms of directive speech acts in the animated film Jumbo. The study used a qualitative approach with descriptive methods. The research data consisted of the characters' utterances containing directive speech acts, with the data source being the dialogue between characters in the animated film Jumbo. Data collection was carried out using listening and note-taking techniques, then analyzed through the stages of identification, classification, interpretation, and drawing conclusions. The results showed 67 data forms of directive speech acts, namely 17 declarative forms, 19 interrogative forms, and 31 imperative forms. The imperative form was the most dominant form. These findings indicate that directive speech acts play a significant role in building interactions between characters and supporting the delivery of moral values ​​in the animated film Jumbo. Keywords: Pragmatics, Directive Speech Acts, Form, Jumbo Animated Film.